Analysis of the Service Connection Process Flow to Achieve Increased Electricity Sales Using an Application Design - Ayyub Nasrah Atmadja; Noviyanti Santoso (Journal Research of Social Science, Economics, and Management, 2026)
The telecommunications industry is crucial for social and economic growth in the digital era, with Indonesia's fixed broadband market expanding rapidly amid intensifying competition among ISPs. PT Telkom Indonesia's Indihome, as market leader with 11,329,973 subscribers in 2025, faces declining market share, which has decreased by an average of 5.13% annually over the past three years to approximately 64%. This study integrates the ISP Service Quality model and Customer Satisfaction Index (CSI) framework to examine how Network Quality, Customer Service, Information Quality, Security, Brand Image, Customer Expectations, Perceived Value, Perceived Price, and Perceived Service Quality affect customer satisfaction and loyalty. Using PLS-SEM with 431 respondents. The results indicate that the proposed model demonstrates a satisfactory level of fit, with an SRMR value of 0.077. The direct effect analysis reveals that NQ, CS, and IQ have positive and significant effects on PSQ. Within the CSI framework, BI, EX, PV, and PSQ are found to have positive and significant effects on CSI, whereas SR and PR do not exhibit significant effects. The findings further indicate that Customer Satisfaction serves as the primary determinant of Customer Loyalty, as evidenced by its positive and significant relationship with Customer Loyalty. In addition, Network Quality and Customer Service emerge as the most influential determinants in shaping Perceived Service Quality within the ISP context, while Customer Expectations represent the strongest determinant of Customer Satisfaction. These findings are expected to provide strategic insights into enhancing service quality and strengthening Customer Loyalty in the increasingly competitive fixed broadband market.